31P NMR studies of an iron-based superconductor Ba0.5Sr0.5Fe2(As1−xPx)2 with Tc = 29 K. (July 2020) - Itoh, Yutaka; Adachi, Seiji
Abstract: We report 31 P NMR studies of an oriented polycrystalline superconductor of Ba0.5 Sr0.5 Fe2 (As1− x P x )2 with x ∼ 0.4 ( T c = 29 K) at T = 14−325 K and B 0 = 1 and 5 T. The 31 P Knight shift Kab at B 0 ⊥ c shows a nearly T -independent uniform spin susceptibility above T c and a spin singlet decrease below T c . The 31 P nuclear spin-lattice relaxation rate 1/ T 1 shows an asymptotic behavior of a + bT ( a and b are constants) at T > 100 K and the minimum at 40 K with an upturn toward T c . The a term in 1/ T 1 indicates the presence of two-dimensional antiferromagnetic spin fluctuations. The negative θ = −15 K of the Curie-Weiss-type antiferromagnetic spin susceptibility χ ( Q ) ∝ 1 / ( T + θ ) in the analysis of 1/ T 1 T suggests antiferromagnetic instability in the superconducting state. Discussions are made from the self-consistent renormalization (SCR) theory for the spin fluctuations with interlayer correlation.